Intelligent automated security surveillance video (i-Assured) / Mohd Razif Shamsuddin, Azlinah Mohamed and Azhar Abdul Rasyid - Shamsuddin, Mohd Razif; Mohamed, Azlinah; Abdul Rasyid, Azhar (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This product is an intelligent human monitoring automated video surveillance. Video surveillance is widely used as a security monitoring tools and usually works as a safety precaution in preventing crime at private housing area and other significant places. However, surveillance system requires high human involvements to assure its functionality and effectiveness towards preventing crime. The main purpose of this product is to reduce human involvement to a minimum when using video surveillance system. Artificial Neural Network (ANN) is applied in this product as a base due to its learning capability in recognizing image pattern which is highly acclaimed. In this research, the Artificial Neural Network will be trained to recognize images of human climbing posture. Furthermore, this research aims to combines ANN with other processing technique in creating a video surveillance prototype which have the ability to detect human climbing posture in regard to prevent robbery. The product is quite easy to use as it requires minimal installation.